The Effect of Responsibility and Leadership on Job Performance of High School at North Jakarta - hamri, hari; Asmawi, Moch.; Rasyid, Unifah (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of this study was to describe and analyze the influence of corporate responsibility, leadership and discipline on job performance. This research used a quantitative approach with survey method. The sample of this research is the whole 120 teachers in High School at North Jakarta is done randomly. The results of the research showed that(1) there is a positive direct influence on responsibility for performance; (2) there is a positive direct effect of leadership on performance; (3) there is a positive direct influence on responsibility for leadership; (4) there is a positive indirect effect of responsibility for performance through leadership. To improve performance, it is necessary to increase responsibility, and leadership. Keywords: Responsibility, Leadership, Job Performance